Medical and psychological rehabilitation of military servicemen (employees): modern organizational trends and regulatory aspects - Denis V. Smirnov; Petr Y. Naumov; Alexander I. Zemlin (Siberian Journal of Life Sciences and Agriculture)
Background. In connection with the military-political events taking place in modern conditions, the participation of the Russian Armed Forces and other troops in maintaining international peace and security in various theaters of operations, the issues of the effectiveness of various types of support for military personnel come to the fore. In conditions where a large number of military personnel (employees) are involved in combat operations and the performance of special tasks, the risk of exposure to adverse factors of military labor and psycho-traumatic events on their health is objectively increased. In the structure of medical support for military personnel (employees), a significant place is occupied by medical and psychological rehabilitation, which is designed to restore the physical and mental health of military personnel through the organization of a complex impact. At the same time, the conceptualization of the organizational and legal foundations for conducting medical and psychological rehabilitation in relation to military personnel (employees) is an urgent scientific task, since it allows: to generalize the existing legal norms and understand the effectiveness of their functioning; identify contradictions and gaps in legal regulation; consolidate various regulatory legal requirements to simplify their understanding and practical application; as well as to improve approaches to maintaining and restoring the health of servicemen and persons equated to them.